Electrocatalytic and selective oxidation of glycerol to formate on 2D 3d-metal phosphate nanosheets and carbon-negative hydrogen generation - Chauhan, Inderjeet; Vijay, Pothoppurathu M.; Ranjan, Ravi; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Materials Au, 2024)
In the landscape of green hydrogen production, alkaline water electrolysis is a well-established, yet not-so-cost-effective, technique due to the high overpotential requirement for the oxygen evolution reaction (OER). A low-voltage approach is proposed to overcome not only the OER challenge by favorably oxidizing abundant feedstock molecules with an earth-abundant catalyst but also to reduce the energy input required for hydrogen production. This alternative process not only generates carbon-negative green H2 but also yields concurrent value-added products (VAPs), thereby maximizing economic advantages and transforming waste into valuable resources. The essence of this study lies in a novel electrocatalyst material. In the present study, unique and two-dimensional (2D) ultrathin nanosheet phosphates featuring first-row transition metals are synthesized by a one-step solvothermal method, and evaluated for the electrocatalytic glycerol oxidation reaction (GLYOR) in an alkaline medium and simultaneous H2 production. Co3(PO4)2 (CoP), Cu3(PO4)2 (CuP), and Ni3(PO4)2 (NiP) exhibit 2D sheet morphologies, while FePO4 (FeP) displays an entirely different snowflake-like morphology. The 2D nanosheet morphology provides a large surface area and a high density of active sites. As a GLYOR catalyst, CoP ultrathin (∼5 nm) nanosheets exhibit remarkably low onset potential at 1.12 V (vs RHE), outperforming that of NiP, FeP, and CuP around 1.25 V (vs RHE). CoP displays 82% selective formate production, indicating a superior capacity for C–C cleavage and concurrent oxidation; this property could be utilized to valorize larger molecules. CoP also exhibits highly sustainable electrochemical stability for a continuous 200 h GLYOR operation, yielding 6.5 L of H2 production with a 4 cm2 electrode and 98 ± 0.5% Faradaic efficiency. The present study advances our understanding of efficient GLYOR catalysts and underscores the potential of sustainable and economically viable green hydrogen production methodologies.